A THE EFFECTIVENESS OF DEDUCTIVE AND INDUCTIVE APPROACHES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE: THE EFFECTIVENESS OF DEDUCTIVE AND INDUCTIVE APPROACHES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Rustamova, Shahnoza (Журнал иностранных языков и лингвистики, 2022)
This article aims investigating the impact of using inductive and deductive approaches of teaching grammar. More specifically, the research also attempts to know the effect of using inductive and deductive teaching of foreign learners’ achievement. I made a research based on inductive and deductive methods in my internship. I chose two groups of pupils for research. They were the pupils who study at secondary school number 41 of Samarkand region Urgut district. First group in the 2th grade was taught by using inductive teaching, the second group in the 5th grade was taught by using deductive teaching. Teacher prepared tests to the pupils of both groups. At the end of the lesson results show differences between inductive and deductive approaches